Inherited haemoglobin variants in a South African population. Issue 4 (April 1987) - Bird, A R; Ellis, P; Wood, K; Mathew, C; Karabus, C
Abstract : We present the findings of a survey to determine the prevalence of inherited haemoglobin disorders in the Coloured (mixed ethnic origin) population of South Africa. A variety of haemoglobins was found. Of the structural variants, Hb E and Hb S were the most common, the former probably originating from South-East Asia and the latter from East Africa and possibly Madagascar. The alpha+ (-alpha) thalassaemia haplotype is particularly common with an observed frequency of 0.023. Beta thalassaemia was rather less common, while hereditary persistence of fetal haemoglobin was found for the first time in this population group, occurring in two subjects.